2016
DOI: 10.1038/srep23269
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Multi-drug Resistance in hepatocellular carcinoma cells is TRPC6/Calcium Dependent

Abstract: Hepatocellular carcinoma (HCC) is notoriously refractory to chemotherapy because of its tendency to develop multi-drug resistance (MDR), whose various underlying mechanisms make it difficult to target. The calcium signalling pathway is associated with many cellular biological activities, and is also a critical player in cancer. However, its role in modulating tumour MDR remains unclear. In this study, stimulation by doxorubicin, hypoxia and ionizing radiation was used to induce MDR in HCC cells. A sustained ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
75
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(78 citation statements)
references
References 57 publications
(70 reference statements)
2
75
0
Order By: Relevance
“…Indeed, global chelation of intracellular free Ca 2+ that attenuates increases in cytosolic free Ca 2+ , suppresses both EGF and hypoxia induced increases in the mesenchymal markers vimentin, N-cadherin and CD44 (Davis et al 2014a). Similar findings have now been reported in Huh7 and HepG2 hepatic cancer cell lines for EMT induced by doxorubicin (Wen et al 2016). It is also now clear that a major remodelling in calcium signalling and the expression of specific calcium permeable ion channels is a feature of EMT and some calcium permeable ion channels are important in the induction of expression of some proteins associated with the mesenchymal phenotype.…”
Section: Calcium Channels and Emt In Cancer Cellssupporting
confidence: 68%
See 1 more Smart Citation
“…Indeed, global chelation of intracellular free Ca 2+ that attenuates increases in cytosolic free Ca 2+ , suppresses both EGF and hypoxia induced increases in the mesenchymal markers vimentin, N-cadherin and CD44 (Davis et al 2014a). Similar findings have now been reported in Huh7 and HepG2 hepatic cancer cell lines for EMT induced by doxorubicin (Wen et al 2016). It is also now clear that a major remodelling in calcium signalling and the expression of specific calcium permeable ion channels is a feature of EMT and some calcium permeable ion channels are important in the induction of expression of some proteins associated with the mesenchymal phenotype.…”
Section: Calcium Channels and Emt In Cancer Cellssupporting
confidence: 68%
“…Consistent with a role for TRPM8 in the maintenance and/or induction of the mesenchymal phenotype in breast cancer cells, overexpression of TRPM8 in the more epithelial like MCF-7 cell line leads to EMT induction as indicated by down regulation of E-cadherin and induction of vimentin (Liu et al 2014). In Huh7 and HepG2 hepatic cancer cells, TRPC6 silencing attenuates changes in the expression of E-cadherin induced by doxorubicin suggesting that in the ability of TRPC6 silencing to increase sensitivity to doxorubicin through effects of resistance pathways may be due at least in part to effects on some aspects of EMT induction (Wen et al 2016).…”
Section: :11mentioning
confidence: 99%
“…Notch activation triggers epithelial-mesenchymal transformation (61). Several studies have revealed that a loss of the epithelial phenotype via epithelial-mesenchymal-transition promotes the acquisition of a stem-like phenotype and drug resistance (62)(63)(64). In addition, in patients with HCC an epithelial gene signature has been associated with sensitivity to the epidermal growth factor receptor inhibitors gefitinib and cetuximab (65).…”
Section: Role Of Notch In Hcc and Icc Developmentmentioning
confidence: 99%
“…Wen et al explored the roles of intracellular calcium on various MDR-relevant mechanisms in HCC cells 54. In their study, HCC cells were treated by stimulation with doxorubicin, hypoxia, and ionizing radiation, representing three models of MDR 54.…”
Section: Drug Resistancementioning
confidence: 99%